The effect of a spiritual care program on the self-esteem of patients with cancer: A quasi-experimental study - Roya Karimi; Ruhollah Mousavizadeh; Shahla Mohammadirizi; Masoud Bahrami (Wolters Kluwer Medknow Publications, 2022)
Background: Despite the importance of self-esteem in cancer patients and the potential role of spiritual care programs in its promotion, no interventional study was found in this field in Iran. The aim of this study was therefore to investigate the effect of a spiritual care program on the self-esteem of patients with various types of cancer. Materials and Methods: This study was quasi-experimental with two groups using a before and after design which was conducted in 2019 in a selected hospital in Isfahan, Iran. A convenience sample of 64 patients randomly assigned into the experimental (n = 32) and the control group (n = 32). Data collection was conducted through a two-part questionnaire including Demographic characteristics and the Coopersmith Self-Esteem Inventory (SEI). The spiritual care program consisted of six sessions based on four domains including individuals' relationship with God, themselves, others, and with the environment. To analyze the data, Chi-square, Fisher's exact test, independent t test, and paired t test were performed. Results: The total self-esteem mean score and its domains were not significantly different between the two groups before the intervention (p > 0.05). However, after conducting the intervention, the total self-esteem mean score and its domains were significantly higher in the intervention group compared with the control group (p < 0.001). Conclusions: The spiritual care program used in this study was effective in promoting the self-esteem of patients with cancer. It is suggested that similar studies are conducted to provide fertile grounds for using such programs in the oncology clinical area.